Pilot study of mobile phone technology in allergic rhinitis in European countries: the MASK‐rhinitis study. Issue 6 (21st February 2017) - Bousquet, J.; Caimmi, D. P.; Bedbrook, A.; Bewick, M.; Hellings, P. W.; Devillier, P.; Arnavielhe, S.; Bachert, C.; Bergmann, K. C.; Canonica, G. W.; Chavannes, N.H.; Cruz, A. A.; et al.
Abstract: Background: The use of Apps running on smartphones and tablets profoundly affects medicine. The MASK‐rhinitis (MACVIA‐ARIA Sentinel NetworK for allergic rhinitis) App ( Allergy Diary ) assesses allergic rhinitis symptoms, disease control and impact on patients' lives. It is freely available in 20 countries (iOS and Android platforms). Aims: To assess in a pilot study whether (i) Allergy Diary users were able to properly provide baseline characteristics (ii) simple phenotypic characteristics based upon data captured by the Allergy Diary could be identified and (iii) information gathered by this study could suggest novel research questions. Methods: The Allergy Diary users were classified into six groups according to the baseline data that they entered into the App: (i) asymptomatic; (ii) nasal symptoms excluding rhinorrhea; (iii) rhinorrhea; (iv) rhinorrhea plus 1–2 nasal/ocular symptoms; (v) rhinorrhea plus ≥3 nasal/ocular symptoms; and (vi) rhinorrhea plus all nasal/ocular symptoms. Results: By 1 June 2016, 3260 users had registered with the Allergy Diary and 2710 had completed the baseline questionnaire. Troublesome symptoms were found mainly in the users with the most symptoms. Around 50% of users with troublesome rhinitis and/or ocular symptoms suffered work impairment. Sleep was impaired by troublesome symptoms and nasal obstruction. Conclusions: This is the first App (iOS and Android) to have tested for allergic rhinitis and conjunctivitis. A simple questionnaire administered by cell phones enables the identification of phenotypic differences between a priori defined rhinitis groups. The results suggest novel concepts and research questions in allergic rhinitis that may not be identified using classical methods.